1991
DOI: 10.1182/blood.v78.2.499.bloodjournal782499
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-alpha overrides the deficient adhesion of chronic myeloid leukemia primitive progenitor cells to bone marrow stromal cells

Abstract: Primitive blast colony-forming cells (BI-CFC) from chronic myeloid leukemia (CML) patients are defective in their attachment to bone marrow-derived stromal cells compared with normal BI-CFC. We investigated the effect of recombinant interferon-alpha 2a (IFN-alpha) on this interaction between hematopoietic progenitor cells and bone marrow-derived stromal cells by culturing normal stromal cells with IFN- alpha (50 to 5,000 U/mL). At 50 U/mL we found that: (1) the capacity of stromal cells to bind two types of CM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 0 publications
1
33
0
Order By: Relevance
“…Similar data have been reported by Verjiaillie et al [27]. Recently, Dowding et al [28] and Osterholz et al [29] showed that interferon-alpha enhances the capacity of marrow stromal cells to bind CML progenitor cells without, indeed, selecting for Ph-negative clonogenic cells. The apparent discrepancy between our report and those of others [28, 291 could be explained either by the presence of interferon-alpha during the adherence procedure with the consequent attachment of a predominantly leukemic clonogenic cell population, or by the use of peripheral blood cells, or by technical differences in the procedure used to harvest stroma non-adherent cells.…”
Section: Discussionsupporting
confidence: 82%
“…Similar data have been reported by Verjiaillie et al [27]. Recently, Dowding et al [28] and Osterholz et al [29] showed that interferon-alpha enhances the capacity of marrow stromal cells to bind CML progenitor cells without, indeed, selecting for Ph-negative clonogenic cells. The apparent discrepancy between our report and those of others [28, 291 could be explained either by the presence of interferon-alpha during the adherence procedure with the consequent attachment of a predominantly leukemic clonogenic cell population, or by the use of peripheral blood cells, or by technical differences in the procedure used to harvest stroma non-adherent cells.…”
Section: Discussionsupporting
confidence: 82%
“…Since IFNα as well as nilotinib were able to increase TNT formation in Kcl-22 cells and IFNα previously have been shown to restore the ability of CML cells ability to bind to fibronectin through restoration of β1 integrin function, we examined β1 integrin as a common feature between the two therapies. 46 Indeed, we found that the change in morphology caused by nilotinib, measured by cellular size, were significantly lower when pre-incubated with a β1 integrin blocking antibody. Also, the induced cell adhesion by both IFNα and nilotinib seemed to involve β1 integrin by significantly increasing the average distance of cell movement when cells were pre-treated with the β1 integrin blocking antibody ( Figure 5C,D).…”
Section: Discussionmentioning
confidence: 77%
“…Cell adherence to fibronectin has previously been found to correlate with TNT formation 30 and treatment of CML cells with IFNα and TKIs have been shown to increase cell adherence to fibronectin, described through a restoration of the β1 integrin by IFNα. 46,48,64,65 To study the role of β1 integrin in cell adherence and TNT formation, we pre-incubated Kcl-22 cells for 30 min with a β1 integrin blocking antibody before treatment for one hour with either IFNα (100 U/mL ) or nilotinib (1 µM). The Kcl-22 cells, without pre-incubation with the β1 integrin blocking antibody (Ctr), showed transformed cell morphology and significantly increased cell surface area on the fibronectin coated surface following nilotinib treatment, whereas IFNα treatment resulted in altered morphology only without significant changes in cell surface area ( Figure 5A,B).…”
Section: Tnt Formation and Increased Cell Surface Adhesion By Drug mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous clinical trails have documented the ability of IFN to induce hematologic and cytogenetic remissions in patients with CML [22]. A number of in vitro effects of IFN-α on CML cells and stroma have been well documented, including inhibition of CML marrow progenitor growth [23,24], restoration of the adherence to stroma [25][26][27], and regulation of stromal cytokine production [28] and cellular immune surveillance [29][30][31][32][33] important in the control of growth of the leukemic clone in CML.…”
Section: Introductionmentioning
confidence: 99%